The viceroy who served as king in South America: Abascal, a radical fidelista to the crown - Pérez Taquio, Jorge Alberto (2021)
Fernando de Abascal y Souza was an unrelenting radical defender of the privileges of the king in the viceroyalty that he had governed for the fortune of Ferdinand VII, who was captive by the French. The viceroy, a man with extensive experience in the military and political spheres, slowed down the separatist efforts within the viceroyalty of Peru as well as outside it, expanding the limits of his viceroyalty, after subduing the revolutionary attempts with blood and fire. Succeeded in safeguarding his majesty's territories from the wave of insurrections that came from Buenos Aires towards Upper Peru, where the outbreaks began, which the viceroy led with great skill, incorporating the territories of Upper Peru, Chile and Quito to the control of Lima, which became the center of the counterrevolution.